2014
DOI: 10.1080/09593330.2014.920421
|View full text |Cite
|
Sign up to set email alerts
|

Impact of seeding on the start-up of one-stage deammonification MBBRs

Abstract: Treating nitrogen-rich reject water from anaerobically digested sludge with deammonification has become a very beneficial side stream process. One common technique is the one-stage moving bed bioreactors (MBBRs), which in comparison with the other deammonification techniques can be started up without seeding anammox bacteria. This study investigated the impact of biofilm seeding on the start-up of one-stage deammonification MBBRs. Two lab-scale reactors were run in parallel with partial nitritation for 56 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…For instance, Klaus et al (2017) observed startup within 120 days in a sidestream ANITA™ Mox MBBR process with AMX biomass inoculation. Kanders et al (2014) showed AMX activity in a sidestream PNA MBBR after 50 days on carriers with a preliminary biofilm of nitrifiers and without AMX biomass inoculation. Given these results, it was expected that AMX establishment on carriers without any AMX biomass inoculation in a mainstream process would take longer than the observed startup times.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Klaus et al (2017) observed startup within 120 days in a sidestream ANITA™ Mox MBBR process with AMX biomass inoculation. Kanders et al (2014) showed AMX activity in a sidestream PNA MBBR after 50 days on carriers with a preliminary biofilm of nitrifiers and without AMX biomass inoculation. Given these results, it was expected that AMX establishment on carriers without any AMX biomass inoculation in a mainstream process would take longer than the observed startup times.…”
Section: Resultsmentioning
confidence: 99%
“…The performance of all three reactors indicates that fast startup of AMX in mainstream MBBRs with no additional AMX biomass seeding is possible. In other experiments involving mainstream and sidestream PNA processes, AMX was inoculated through biomass or carrier seeding (Kanders et al, 2014; Klaus et al, 2017), so it was unknown how long it would take for AMX activity to begin in a mainstream reactor without any AMX biomass seeding. For instance, Klaus et al (2017) observed startup within 120 days in a sidestream ANITA™ Mox MBBR process with AMX biomass inoculation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometime NOB activity may increase again after changing operation pattern even under low NOB abundant56. If NOB contamination was serious, the problem of nitrate build-up could be simply solved only by discarding the sludge with more NOB and reinoculation, if enough seeding sludge with anammox bacteria was available conveniently26.…”
Section: Discussionmentioning
confidence: 99%
“…According to Christensson et al (2013) and Lemaire et al (2011), seeding decreases startup time, while Kanders et al (2014) and Ling (2009) argue that seeding is not necessary. Regardless of seeding influence on startup time, seeding provides the benefit of immediate nitrite consumption by AMX, which allows for a higher initial ammonia load and reduced risk of nitrite inhibition (Kanders et al, 2014). Startup of the deammonification MBBR was limited by AMX due to their slow growth rate and sensitivity to nitrite.…”
Section: Resultsmentioning
confidence: 99%